Pergamon, Türkei: Restaurierung - Bachmann, Martin (e-Forschungsberichte des DAI, 2023)
The restoration work in Pergamon focusses on two key monuments of the Ancient City: The Red Hall in the Roman lower town and the Gymnasium at the castle hill of Pergamon. Both structures are of outstanding importance as ancient monuments, but also as utmost components of a future, holistic visitors plan for Pergamon. In the Red Hall works have been carried out since 2006 and started initially with the southern round tower. This was followed in 2009 by the substructures in the southeast corner of the temenos and the reconstruction of a large figural support in the southern courtyard, which was completed in 2013. The work on the substructures is to be continued, at the same time current restoration works on the great basilica and the northern round tower initiated by the Turkish Ministry of Culture are advised by the DAI. In the Gymnasium a new project has been started in 2012 with the aim of consolidating the ruins and removing rubble from the old excavations. This covers parts of the structure and locks the ancient road adjoining the Gymnasium, a significant impairment for the visit of the town hill. The mound has already been largely removed and parts of the structure have been preserved. The worked sections provide a some signaling effect, while a consinderbale part still needs to be done.